Positive electrode material for electric device, and positive electrode for electric device and electric device using the same

By incorporating a solid electrolyte and sulfur within the pores of a conductive material in lithium secondary batteries, the internal resistance is reduced, addressing the limitations of charge/discharge rate characteristics and energy density in existing sulfur-based batteries.

JP7662988B2Active Publication Date: 2025-04-16NISSAN MOTOR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021011945
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-28
Publication Date
2025-04-16
Estimated Expiration
2041-01-28

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face challenges in achieving sufficient charge/discharge rate characteristics and high energy density due to high internal resistance, particularly when using sulfur as a positive electrode active material.

Method used

A positive electrode material comprising a conductive material with pores, a solid electrolyte, and sulfur as the positive electrode active material, where the solid electrolyte and sulfur are arranged on the inner surface of the pores, and the pore volume distribution is controlled to minimize small pore volumes, thereby reducing internal resistance.

Benefits of technology

The proposed solution significantly reduces the internal resistance of lithium secondary batteries, enhancing their charge/discharge rate characteristics and energy density, particularly when using sulfur as the positive electrode active material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662988000002
    Figure 0007662988000002
  • Figure 0007662988000003
    Figure 0007662988000003
  • Figure 0007662988000004
    Figure 0007662988000004
Patent Text Reader

Abstract

To provide means for further reducing the internal resistance of an electrical device using a positive electrode active material containing sulfur.SOLUTION: In a positive electrode material including a conductive material having pores, a solid electrolyte, and a positive electrode active material containing sulfur, at least a part of the solid electrolyte and at least a part of the positive electrode active material are arranged on the inner surface of a pore so as to be in contact with each other, and as the conductive material, the percentage of the pore volume of pores having a pore diameter in the range of 1 to 4 nm to the pore volume of pores having a pore diameter in the range of 1 to 100 nm is 20% or less.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode material for an electric device, and a positive electrode for an electric device and an electric device each using the same. [Background technology]

[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there are high hopes for a reduction in carbon dioxide emissions through the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and there has been active development of non-aqueous electrolyte secondary batteries, such as motor drive secondary batteries, which hold the key to putting these into practical use.

[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.

[0004] Currently, lithium secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and these liquid-based lithium secondary batteries require stricter safety measures against leakage, short circuits, overcharging, etc. than other batteries.

[0005] In recent years, research and development of all-solid-state lithium secondary batteries using oxide-based or sulfide-based solid electrolytes has been actively conducted. A solid electrolyte is a material that is mainly composed of an ion conductor capable of ion conduction in a solid state. Therefore, in principle, all-solid-state lithium secondary batteries do not have various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium secondary batteries. In addition, in general, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials can significantly improve the output density and energy density of the battery. For example, elemental sulfur (S8) has an extremely large theoretical capacity of about 1670 mAh / g, and has the advantages of being low cost and abundant in resources.

[0006] On the other hand, metallic lithium, which is a negative electrode active material that supplies lithium ions to a positive electrode, is known as a high-capacity negative electrode material that can be used in all-solid-state batteries. However, in all-solid-state batteries that use metallic lithium as the negative electrode active material and a sulfide solid electrolyte as the solid electrolyte, the metallic lithium and the sulfide solid electrolyte may react with each other, resulting in a deterioration in battery characteristics.

[0007] In order to address such problems, Patent Document 1 proposes a technique of using a composite material containing a conductive agent and an alkali metal sulfide integrated on the surface of the conductive agent as a positive electrode material for an all-solid-state battery. Patent Document 1 claims that by using a positive electrode material having such a configuration, a positive electrode material and a lithium-ion battery are provided that have a high theoretical capacity and can use a negative electrode active material that does not supply lithium ions to the positive electrode. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2012 / 102037 Brochure Summary of the Invention [Problem to be solved by the invention]

[0009] Depending on the application of the secondary battery, it is required that sufficient capacity can be obtained when charging and discharging at a high charge and discharge rate (i.e., the so-called charge and discharge rate characteristics are sufficient). For example, a secondary battery with insufficient charge and discharge rate characteristics cannot utilize sufficient capacity in response to rapid charging and discharging. In order to improve the charge and discharge rate characteristics of the secondary battery, it is necessary to reduce the internal resistance of the battery.

[0010] Therefore, an object of the present invention is to provide a means for further reducing the internal resistance of an electric device that uses a positive electrode active material containing sulfur. [Means for solving the problem]

[0011] The present inventors have conducted intensive research to solve the above problems, and as a result, have found that the above problems can be solved by configuring a cathode material including a conductive material having pores, a solid electrolyte, and a cathode active material containing sulfur so that the solid electrolyte and the cathode active material are arranged on the inner surfaces of the pores so as to be in contact with each other, and by appropriately controlling the profile of the pore volume of the conductive material, thereby completing the present invention.

[0012] One embodiment of the present invention is a positive electrode material for an electric device, comprising: a conductive material having pores; a solid electrolyte; and a positive electrode active material containing sulfur, wherein at least a part of the solid electrolyte and at least a part of the positive electrode active material are disposed on inner surfaces of the pores so as to be in contact with each other; and wherein a percentage of a pore volume of pores having a pore diameter in the range of 1 to 4 nm relative to a pore volume of pores having a pore diameter in the range of 1 to 100 nm is 20% or less. Effect of the Invention

[0013] According to the present invention, in an electric device using a positive electrode active material containing sulfur, the internal resistance of the electric device can be further reduced. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a perspective view showing the appearance of a flat laminate-type all-solid-state lithium secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. [Figure 3A] FIG. 3A is a cross-sectional schematic diagram of a positive electrode material in the prior art. [Figure 3B] FIG. 3B is a cross-sectional schematic diagram of a positive electrode material according to one embodiment of the present invention. [Figure 4]FIG. 4 is a graph showing the pore size distribution in the range of 1 to 100 nm, measured according to the BJH method, for the carbons used in the comparative examples and examples described later. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the claims, and is not limited to only the following embodiment. The dimensional ratios in the drawings are exaggerated for convenience of explanation and may differ from the actual ratios. Hereinafter, the present invention will be described by taking as an example a stacked type (internal parallel connection type) all-solid-state lithium secondary battery, which is one form of secondary battery. As described above, the solid electrolyte constituting the all-solid-state lithium secondary battery is a material mainly composed of an ion conductor capable of ion conduction in a solid. For this reason, the all-solid-state lithium secondary battery has the advantage that, in principle, various problems caused by a flammable organic electrolyte do not occur as in the conventional liquid-based lithium secondary battery. In addition, in general, there is also the advantage that the output density and energy density of the battery can be significantly improved by using a high-potential, large-capacity positive electrode material and a large-capacity negative electrode material.

[0016] One embodiment of the present invention is a positive electrode material for an electric device, comprising a conductive material having pores, a solid electrolyte, and a positive electrode active material containing sulfur, wherein at least a part of the solid electrolyte and at least a part of the positive electrode active material are disposed on the inner surfaces of the pores so as to be in contact with each other, and the percentage of the pore volume of pores having a pore diameter in the range of 1 to 4 nm to the pore volume of pores having a pore diameter in the range of 1 to 100 nm is 20% or less. The positive electrode material for an electric device according to this embodiment can further reduce the internal resistance of the electric device.

[0017] FIG. 1 is a perspective view showing the appearance of a flat laminated type all-solid-state lithium secondary battery according to one embodiment of the present invention. FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. 1. The laminated type allows the battery to be compact and have a high capacity. In this specification, the flat laminated type non-bipolar lithium secondary battery (hereinafter also simply referred to as a "laminated type battery") shown in FIG. 1 and FIG. 2 will be described in detail as an example. However, in terms of the internal electrical connection form (electrode structure) of the lithium secondary battery according to this embodiment, it can be applied to both non-bipolar type (internal parallel connection type) batteries and bipolar type (internal series connection type) batteries.

[0018] 1, the stacked battery 10a has a flat rectangular shape, with a negative electrode current collector 25 and a positive electrode current collector 27 for extracting electric power extending from both sides. The power generating element 21 is wrapped in a battery exterior material (laminate film 29) of the stacked battery 10a, and the periphery is heat-sealed, with the power generating element 21 being sealed with the negative electrode current collector 25 and the positive electrode current collector 27 extending to the outside.

[0019] The lithium secondary battery according to the present embodiment is not limited to a laminated flat shape. A wound lithium secondary battery may be cylindrical, or may be a rectangular flat shape obtained by deforming such a cylindrical shape, and is not particularly limited. The cylindrical shape may be a laminate film or a conventional cylindrical can (metal can) as an exterior material, and is not particularly limited. Preferably, the power generating element is housed inside a laminate film containing aluminum. This form can achieve weight reduction.

[0020] There is also no particular limitation on the removal of the current collectors (25, 27) shown in Fig. 1. The negative current collector 25 and the positive current collector 27 may be pulled out from the same side, or the negative current collector 25 and the positive current collector 27 may each be divided into a plurality of pieces and removed from each side, and are not limited to what is shown in Fig. 1. In addition, in a wound lithium battery, the terminals may be formed using, for example, a cylindrical can (metal can) instead of a tab.

[0021] 2, the stacked battery 10a of this embodiment has a structure in which a flat, generally rectangular power generating element 21, where charge and discharge reactions actually proceed, is sealed inside a laminate film 29, which is a battery exterior material. Here, the power generating element 21 has a structure in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are laminated. The positive electrode has a structure in which positive electrode active material layers 15 containing a positive electrode active material are disposed on both sides of a positive electrode collector 11". The negative electrode has a structure in which negative electrode active material layers 13 containing a negative electrode active material are disposed on both sides of a negative electrode collector 11'. Specifically, the positive electrode, solid electrolyte layer, and negative electrode are stacked in this order such that one positive electrode active material layer 15 and an adjacent negative electrode active material layer 13 face each other with a solid electrolyte layer 17 interposed therebetween. As a result, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute one unit cell layer 19. Therefore, it can be said that the stacked battery 10a shown in FIG. 1 has a structure in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel.

[0022] As shown in FIG. 2, the outermost negative electrode current collectors located on both outermost layers of the power generating element 21 each have a negative electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. In other words, instead of using a current collector exclusively for the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as it is as the outermost layer current collector. In some cases, the negative electrode active material layer 13 and the positive electrode active material layer 15 may be used as the negative electrode and positive electrode, respectively, without using the current collectors (11', 11").

[0023] Negative current collector 11′ and positive current collector 11″ are respectively attached with negative current collector plate (tab) 25 and positive current collector plate (tab) 27 that are electrically connected to the respective electrodes (positive and negative electrodes), and have a structure in which they are sandwiched between ends of laminate film 29, which is a battery exterior material, and are led out of laminate film 29. Positive current collector 27 and negative current collector 25 may be attached to positive current collector 11″ and negative current collector 11′ of each electrode by ultrasonic welding, resistance welding, or the like, respectively, via positive electrode leads and negative electrode leads (not shown) as necessary.

[0024] The main components of the lithium secondary battery according to this embodiment will be described below.

[0025] [Current collector] The current collector has a function of mediating the movement of electrons from the electrode active material layer. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.

[0026] Specifically, the metal may be aluminum, nickel, iron, stainless steel, titanium, copper, etc. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, etc. may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferable from the viewpoint of electronic conductivity, battery operating potential, adhesion of the negative electrode active material by sputtering to the current collector, etc.

[0027] The latter conductive resin may be a conductive polymer material or a non-conductive polymer material to which a conductive filler is added as required.

[0028] Examples of non-conductive polymeric materials include polyethylene (PE; high density polyethylene (HDPE), low density polyethylene (LDPE), etc.), polypropylene (PP), polyethylene terephthalate (PET), polyethernitrile (PEN), polyimide (PI), polyamideimide (PAI), polyamide (PA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyvinylidene fluoride (PVdF), polystyrene (PS), etc. Such non-conductive polymeric materials can have excellent electric potential resistance or solvent resistance.

[0029] A conductive filler may be added to the conductive polymer material or non-conductive polymer material as necessary. In particular, when the resin serving as the base material of the current collector is made of only a non-conductive polymer, a conductive filler is necessarily required to impart conductivity to the resin.

[0030] The conductive filler can be used without any particular limitation as long as it is a material having electrical conductivity. For example, metals and conductive carbons can be mentioned as materials having excellent electrical conductivity, potential resistance, or lithium ion blocking properties. The metal is not particularly limited, but preferably contains at least one metal selected from the group consisting of Ni, Ti, Al, Cu, Pt, Fe, Cr, Sn, Zn, In, and Sb, or an alloy or metal oxide containing these metals. The conductive carbon is also not particularly limited. Preferably, it contains at least one selected from the group consisting of acetylene black, Vulcan (registered trademark), Black Pearl (registered trademark), carbon nanofiber, Ketjen Black (registered trademark), carbon nanotube, carbon nanohorn, carbon nanoballoon, and fullerene.

[0031] The amount of conductive filler added is not particularly limited as long as it is an amount that can impart sufficient conductivity to the current collector, and is generally 5 to 80 mass % relative to the total mass of the current collector (100 mass %).

[0032] The current collector may have a single layer structure made of a single material, or may have a laminate structure in which layers made of these materials are appropriately combined. From the viewpoint of reducing the weight of the current collector, it is preferable to include at least a conductive resin layer made of a resin having conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. Furthermore, if the negative electrode active material layer and the positive electrode active material layer described later are conductive by themselves and can perform a current collecting function, it is not necessary to use a current collector as a member separate from these electrode active material layers. In such a form, the negative electrode active material layer described later constitutes the negative electrode as it is, and the positive electrode active material layer described later constitutes the positive electrode as it is.

[0033] [Negative electrode (negative electrode active material layer)] In the stacked battery according to the embodiment shown in Fig. 1 and Fig. 2, the negative electrode active material layer 13 contains a negative electrode active material. The type of the negative electrode active material is not particularly limited, but may include a carbon material, a metal oxide, and a metal active material. Examples of the carbon material include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon. Examples of the metal oxide include Nb2O5, Li4Ti5O 12 and the like. Furthermore, silicon-based negative electrode active materials and tin-based negative electrode active materials may be used. Here, silicon and tin belong to the 14th group of elements, and are known to be negative electrode active materials that can greatly improve the capacity of non-aqueous electrolyte secondary batteries. These simple substances can absorb and release a large number of charge carriers (lithium ions, etc.) per unit volume (mass), and therefore become high-capacity negative electrode active materials. Here, it is preferable to use Si simple substance as the silicon-based negative electrode active material. Similarly, SiO 2 disproportionated into two phases, a Si phase and a silicon oxide phase, is also used. xIt is also preferable to use silicon oxides such as (0.3≦x≦1.6). In this case, the range of x is more preferably 0.5≦x≦1.5, and even more preferably 0.7≦x≦1.2. Furthermore, an alloy containing silicon (silicon-containing alloy-based negative electrode active material) may be used. On the other hand, examples of negative electrode active materials containing tin element (tin-based negative electrode active materials) include simple Sn, tin alloys (Cu-Sn alloys, Co-Sn alloys), amorphous tin oxides, tin silicon oxides, and the like. Among these, examples of amorphous tin oxides include SnB 0.4 P 0.6 O 3.1 Examples of the tin silicon oxide include SnSiO3. Metals containing lithium may be used as the negative electrode active material. Such negative electrode active materials are not particularly limited as long as they are active materials containing lithium, and examples thereof include metallic lithium and lithium-containing alloys. Examples of the lithium-containing alloys include alloys of Li and at least one of In, Al, Si, and Sn. In some cases, two or more negative electrode active materials may be used in combination. Of course, negative electrode active materials other than the above may be used. The negative electrode active material preferably contains metallic lithium, a silicon-based negative electrode active material, or a tin-based negative electrode active material, and particularly preferably contains metallic lithium.

[0034] The shape of the negative electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the negative electrode active material is particulate, its average particle size (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.

[0035] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 99 mass %, and more preferably in the range of 50 to 90 mass %.

[0036] The negative electrode active material layer preferably further includes a solid electrolyte. By including the solid electrolyte in the negative electrode active material layer, the ionic conductivity of the negative electrode active material layer can be improved. Examples of the solid electrolyte include sulfide solid electrolytes and oxide solid electrolytes, and the sulfide solid electrolyte is preferable.

[0037] Examples of sulfide solid electrolytes include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS4, Li3PS4, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In). The description "Li2S-P2S5" means a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.

[0038] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. Examples of sulfide solid electrolytes having a Li4P2S7 skeleton include Li-PS solid electrolytes called LPS (for example, Li7P3S 11) can be mentioned. Also, as the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P x S4 (where x satisfies 0 < x < 1), such as LGPS, may be used. Among them, the sulfide solid electrolyte contained in the active material layer is preferably a sulfide solid electrolyte containing P element, and the sulfide solid electrolyte is more preferably a material mainly composed of Li2S - P2S5. Furthermore, the sulfide solid electrolyte may contain halogen (F, Cl, Br, I). In a preferred embodiment, the sulfide solid electrolyte contains Li6PS5X (where X is Cl, Br or I, preferably Cl).

[0039] Also, when the sulfide solid electrolyte is of the Li2S - P2S5 system, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5 = 50:50 to 100:0 in terms of molar ratio, and more preferably Li2S:P2S5 = 70:30 to 80:20.

[0040] Also, the sulfide solid electrolyte may be a sulfide glass, a crystallized sulfide glass, or a crystalline material obtained by a solid phase method. The sulfide glass can be obtained, for example, by performing mechanical milling (such as a ball mill) on the raw material composition. Also, the crystallized sulfide glass can be obtained, for example, by performing heat treatment on the sulfide glass at a temperature above the crystallization temperature. Also, the ionic conductivity (for example, Li ion conductivity) of the sulfide solid electrolyte at room temperature (25°C) is, for example, 1×10 -5 S / cm or more is preferred, and 1×10 -4 S / cm or more is more preferred. The value of the ionic conductivity of the solid electrolyte can be measured by the AC impedance method.

[0041] Examples of the oxide solid electrolyte include compounds having a NASICON-type structure. As an example of a compound having a NASICON-type structure, the general formula Li 1+x Al x Ge 2-xCompounds represented by the formula (PO4)3 (0≦x≦2) (LAGP), general formula Li 1+x Al x Ti 2-x (PO4)3 (0≦x≦2) (LATP) and the like. Another example of an oxide solid electrolyte is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.

[0042] The shape of the solid electrolyte may be, for example, a particulate shape such as a spherical shape or an oval spherical shape, or a thin film shape. When the solid electrolyte is particulate, its average particle diameter (D 50 ) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. 50 ) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.

[0043] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, and more preferably in the range of 10 to 50 mass %.

[0044] The negative electrode active material layer may further contain at least one of a conductive assistant and a binder, in addition to the above-mentioned negative electrode active material and solid electrolyte.

[0045] Examples of the conductive assistant include metals such as aluminum, stainless steel (SUS), silver, gold, copper, and titanium, alloys or metal oxides containing these metals; carbon fibers (specifically, vapor-grown carbon fibers (VGCF), polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, rayon-based carbon fibers, activated carbon fibers, etc.), carbon nanotubes (CNTs), and carbon black (specifically, acetylene black, Ketjen Black (registered trademark), furnace black, channel black, thermal lamp black, etc.), but are not limited thereto. In addition, a particulate ceramic material or a resin material coated with the above-mentioned metal material by plating or the like can also be used as a conductive assistant. Among these conductive assistants, from the viewpoint of electrical stability, it is preferable to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, copper, titanium, and carbon, more preferably to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, and carbon, and even more preferably to include at least one carbon. These conductive assistants may be used alone or in combination of two or more.

[0046] The conductive assistant is preferably in the form of particles or fibers. When the conductive assistant is in the form of particles, the shape of the particles is not particularly limited, and may be any shape such as powder, sphere, rod, needle, plate, column, irregular shape, scale, spindle shape, etc.

[0047] When the conductive assistant is particulate, the average particle diameter (primary particle diameter) is not particularly limited, but is preferably 0.01 to 10 μm from the viewpoint of the electrical properties of the battery. In this specification, the "particle diameter of the conductive assistant" means the maximum distance L between any two points on the contour line of the conductive assistant. The value of the "average particle diameter of the conductive assistant" is calculated as the average value of particle diameters of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0048] When the negative electrode active material layer contains a conductive assistant, the content of the conductive assistant in the negative electrode active material layer is not particularly limited, but is preferably 0 to 10 mass%, more preferably 2 to 8 mass%, and further preferably 4 to 7 mass% relative to the total mass of the negative electrode active material layer. If the content is within such a range, a stronger electron conduction path can be formed in the negative electrode active material layer, which can effectively contribute to improving the battery characteristics.

[0049] On the other hand, the binder is not particularly limited, but examples thereof include the following materials:

[0050] Thermoplastic polymers such as polybutylene terephthalate, polyethylene terephthalate, polyvinylidene fluoride (PVDF) (including compounds in which hydrogen atoms are replaced by other halogen elements), polyethylene, polypropylene, polymethylpentene, polybutene, polyether nitrile, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, ethylene-vinyl acetate copolymer, polyvinyl chloride, styrene-butadiene rubber (SBR), ethylene-propylene-diene copolymer, styrene-butadiene-styrene block copolymer and its hydrogenated derivatives, styrene-isoprene-styrene block copolymer and its hydrogenated derivatives, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), ethylene Examples of such fluororesins include ethylene-chlorotrifluoroethylene copolymer (ECTFE) and polyvinyl fluoride (PVF), vinylidene fluoride-hexafluoropropylene-based fluororubber (VDF-HFP-based fluororubber), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-HFP-TFE-based fluororubber), vinylidene fluoride-pentafluoropropylene-based fluororubber (VDF-PFP-based fluororubber), vinylidene fluoride-pentafluoropropylene-tetrafluoroethylene-based fluororubber (VDF-PFP-TFE-based fluororubber), vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene-based fluororubber (VDF-PFMVE-TFE-based fluororubber), and vinylidene fluoride-chlorotrifluoroethylene-based fluororubber (VDF-CTFE-based fluororubber), as well as epoxy resins. Among these, polyimide, styrene-butadiene rubber, carboxymethyl cellulose, polypropylene, polytetrafluoroethylene, polyacrylonitrile, and polyamide are more preferable.

[0051] The thickness of the negative electrode active material layer differs depending on the intended configuration of the secondary battery, but is preferably within the range of, for example, 0.1 to 1000 μm.

[0052] [Solid electrolyte layer] In the stacked battery according to the embodiment shown in FIGS. 1 and 2, the solid electrolyte layer is interposed between the above-mentioned positive electrode active material layer and negative electrode active material layer, and is a layer that essentially contains a solid electrolyte.

[0053] The specific form of the solid electrolyte contained in the solid electrolyte layer is not particularly limited, and the solid electrolytes exemplified in the section on the negative electrode active material layer and their preferred forms can be similarly adopted. In some cases, a solid electrolyte other than the above-mentioned solid electrolytes may be used in combination.

[0054] The solid electrolyte layer may further contain a binder in addition to the above-mentioned predetermined solid electrolyte. For the binder that can be contained in the solid electrolyte layer, the examples and preferred forms described in the section on the negative electrode active material layer can be similarly adopted.

[0055] The thickness of the solid electrolyte layer varies depending on the configuration of the intended lithium secondary battery, but from the viewpoint of improving the volumetric energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. On the other hand, there is no particular restriction on the lower limit of the thickness of the solid electrolyte layer, but it is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more.

[0056] [Cathode active material layer] 1 and 2, the positive electrode active material layer contains a positive electrode material for an electric device according to one embodiment of the present invention. The positive electrode material for an electric device contains a conductive material having pores, a solid electrolyte, and a positive electrode active material containing sulfur.

[0057] (Positive electrode active material containing sulfur) The type of the positive electrode active material containing sulfur is not particularly limited, but may be, in addition to elemental sulfur (S), particles or thin films of organic or inorganic sulfur compounds, and may be any material capable of releasing lithium ions during charging and absorbing lithium ions during discharging by utilizing the oxidation-reduction reaction of sulfur. Examples of the organic sulfur compound include disulfide compounds, sulfur-modified polyacrylonitrile, sulfur-modified polyisoprene, rubeanic acid (dithiooxamide), polycarbonate sulfide, and the like, as typified by the compounds described in the pamphlet of International Publication No. 2010 / 044437. Among these, disulfide compounds, sulfur-modified polyacrylonitrile, and rubeanic acid are preferred, and sulfur-modified polyacrylonitrile is particularly preferred. As the disulfide compound, those having a dithiobiurea derivative, a thiourea group, a thioisocyanate, or a thioamide group are more preferred. Here, the sulfur-modified polyacrylonitrile is a modified polyacrylonitrile containing sulfur atoms, which is obtained by mixing sulfur powder with polyacrylonitrile and heating the mixture under an inert gas or under reduced pressure. Its estimated structure is, for example, as shown in Chem. Mater. 2011, 23, 5024-5028, in which polyacrylonitrile is ring-closed to form a polycyclic ring, and at least a part of S is bonded to C. The compound described in this document has a peak at 1330 cm in the Raman spectrum. -1 and 1560cm -1 There is a strong peak signal near 307 cm -1 , 379cm -1 , 472cm -1 , 929cm -1There is a peak around 1000 nm. On the other hand, inorganic sulfur compounds are preferred because of their excellent stability, and specific examples thereof include sulfur element (S), TiS2, TiS3, TiS4, NiS, NiS2, CuS, FeS2, Li2S, MoS2, MoS3, MnS, MnS2, CoS, CoS2, and the like. Among them, S, S-carbon composite, TiS2, TiS3, TiS4, FeS2, and MoS2 are preferred, sulfur element (S), TiS2, and FeS2 are more preferred, and sulfur element (S) is particularly preferred from the viewpoint of high capacity. As the sulfur element (S), α-sulfur, β-sulfur, or γ-sulfur having an S8 structure can be used.

[0058] The positive electrode material according to the present embodiment may further include a positive electrode active material that does not contain sulfur in addition to the positive electrode active material that contains sulfur. Examples of the positive electrode active material that does not contain sulfur include layered rock salt type active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, and Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of oxide active materials other than those mentioned above include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li4Ti5O 12 Examples include:

[0059] In some cases, two or more kinds of positive electrode active materials may be used in combination. Of course, other positive electrode active materials than those mentioned above may be used. However, the content ratio of the positive electrode active material containing sulfur in the total amount of the positive electrode active material (100% by mass) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.

[0060] (solid electrolyte) The positive electrode material according to the present embodiment essentially contains a solid electrolyte. There is no particular limitation on the specific form of the solid electrolyte contained in the positive electrode material according to the present embodiment, and the solid electrolytes exemplified in the section on the negative electrode active material layer and their preferred forms can be similarly adopted. In some cases, a solid electrolyte other than the above-mentioned solid electrolytes may be used in combination.

[0061] In particular, the solid electrolyte contained in the positive electrode material according to this embodiment is preferably a sulfide solid electrolyte. In another preferred embodiment, the solid electrolyte contained in the solid electrolyte layer contains an alkali metal atom. Here, examples of the alkali metal that can be contained in the solid electrolyte include Li, Na, and K, and Li is preferred in terms of its excellent ion conductivity. In yet another preferred embodiment, the solid electrolyte contained in the positive electrode material contains an alkali metal atom (e.g., Li, Na, or K; preferably Li) and a phosphorus atom and / or a boron atom. Examples of sulfide solid electrolytes containing such alkali metal atoms and phosphorus and / or boron atoms include LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS4, Li3PS4, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-SiS2-Li3PO4, etc. Examples of sulfide solid electrolytes having a Li4P2S7 skeleton include Li-PS-based solid electrolytes called LPS (for example, Li7P3S 11 ) can be mentioned. For example, Li (4-x) Ge (1-x) P xAn LGPS or the like represented by S4 (where 0 < x < 1) may be used. Among them, the sulfide solid electrolyte contained in the active material layer is preferably a sulfide solid electrolyte containing a phosphorus atom, and more preferably, the sulfide solid electrolyte is a material mainly composed of Li2S-P2S5. Further, the sulfide solid electrolyte may contain a halogen (F, Cl, Br, I). In a preferred embodiment, the sulfide solid electrolyte contains Li6PS5X (where X is Cl, Br or I, preferably Cl). Since these solid electrolytes have high ionic conductivity, they can also effectively contribute to the manifestation of the effects of the present invention.

[0062] (Conductive material) The positive electrode material according to this embodiment essentially contains a conductive material having pores. Regarding the specific form of the conductive material contained in the positive electrode material according to this embodiment, there is no particular limitation as long as it is a conductive material having pores and has a predetermined pore volume profile described later, and conventionally known materials can be appropriately adopted. From the viewpoints of excellent conductivity, ease of processing, and easy design of a desired pore distribution, the conductive material having pores is preferably a carbon material.

[0063] Examples of the carbon material having pores include carbon black such as activated carbon, Ketjenblack (registered trademark) (highly conductive carbon black), (oil) furnace black, channel black, acetylene black, thermal black, lamp black, carbon particles (carbon carriers) such as coke, natural graphite, and artificial graphite. Note that the carbon material preferably has carbon as its main component. Here, "having carbon as the main component" means containing carbon atoms as the main component, and includes both the concept of consisting only of carbon atoms and substantially consisting of carbon atoms. "Substantially consisting of carbon atoms" means that the incorporation of impurities of about 2 to 3 mass% or less is allowable.

[0064] The positive electrode material according to the present embodiment is characterized in that the percentage of the pore volume of pores having a pore diameter in the range of 1 to 4 nm to the pore volume of pores having a pore diameter in the range of 1 to 100 nm (mesopores) is 20% or less among the pores of the conductive material having pores. Qualitatively speaking, this characteristic means that the proportion of the pore volume occupied by pores having a relatively small pore diameter is small. Here, in this specification, the pore distribution (pore volume value) of the mesopores of the conductive material is obtained by the BJH method. The "BJH method" is an abbreviation of the "Barrett-Joyner-Halenda method" and is a method for obtaining the pore distribution of mesopores (pore diameter 1 to 100 nm). The total adsorption amount is expressed as the sum of the multilayer adsorption amount and the capillary condensation amount. Of these, capillary condensation is a phenomenon that usually occurs in extremely small pores, but in the mesopore region with a large pore diameter, it is considered that capillary condensation occurs in the gaps between molecules left after the multilayer adsorption layer is completed, and the pore distribution of the mesopores is analyzed from the thickness of the multimolecular adsorption layer at the time when capillary condensation occurs. Details of the BJH method are described in EP Barrett, LG Joyner and PP H Alenda, J. Am. Chem. Soc., 73, 373 (1951). From the viewpoint of further exerting the effect of reducing internal resistance, the above percentage value is preferably 18% or less, more preferably 15% or less, even more preferably 12% or less, and particularly preferably 9%. On the other hand, there is no particular restriction on the lower limit of the above percentage, but it is, for example, 3% or more.

[0065] The BET specific surface area of ​​the porous conductive material (preferably a carbon material) is 200 m 2 / g or more, and 2 / g or more is more preferable, and 800m 2 / g or more is more preferable, and 1200m 2 / g or more is particularly preferable, and 1500m 2It is most preferable that it is / g or more. Further, the total pore volume of the conductive material (preferably a carbon material) having pores is preferably 1.0 mL / g or more, more preferably 1.3 mL / g or more, and even more preferably 1.5 mL / g or more. If the BET specific surface area and the total pore volume of the conductive material are within such ranges, a sufficient amount of pores can be retained, and thus a sufficient amount of the positive electrode active material can be retained. Note that the values of the BET specific surface area and the total pore volume of the conductive material can be measured by nitrogen adsorption / desorption measurement. This nitrogen adsorption / desorption measurement is performed using BELSORP mini manufactured by MicrotracBEL Corporation at a temperature of -196°C by the multipoint method. The BET specific surface area is determined from the adsorption isotherm in the relative pressure range of 0.01 < P / P0 < 0.05. Further, the pore volume is determined from the volume of adsorbed N2 at a relative pressure of 0.96.

[0066] The average pore diameter of the conductive material is not particularly limited, but is preferably 50 nm or less, and particularly preferably 30 nm or less. If the average pore diameter of the conductive material is within these ranges, electrons can be sufficiently supplied to the active material existing at a position away from the pore wall among the positive electrode active materials containing sulfur disposed inside the pores. Note that the value of the average pore diameter of the conductive material can be calculated by nitrogen adsorption / desorption measurement in the same manner as when obtaining the values of the BET specific surface area and the pore volume.

[0067] When the conductive material is in a particulate form, the average particle diameter (primary particle diameter) is not particularly limited, but is preferably 0.05 to 50 μm, more preferably 0.1 to 20 μm, and even more preferably 0.5 to 10 μm. Note that as the definition of the "particle diameter of the conductive material" and the measurement method of the "average particle diameter of the conductive material", those described above for the conductive aid are similarly adopted.

[0068] As described above, the positive electrode material according to the present embodiment includes a conductive material having pores, a solid electrolyte, and a positive electrode active material containing sulfur, and is characterized in that at least a portion of the solid electrolyte and at least a portion of the positive electrode active material are disposed on the inner surfaces of the pores of the conductive material so as to be in contact with each other.

[0069] FIG. 3A is a schematic cross-sectional view of a cathode material 100' in the prior art. FIG. 3B is a schematic cross-sectional view of a cathode material 100 according to one embodiment of the present invention. In FIG. 3A and FIG. 3B, a carbon material (e.g., activated carbon) 110, which is a conductive material, has a large number of pores 110a. The inside of the pores 110a is filled with sulfur 120, which is a cathode active material. The cathode active material (sulfur) 120 is also disposed on the surface of the carbon material (activated carbon) 110. Here, in the cathode material 100' according to the prior art shown in FIG. 3A, a solid electrolyte (e.g., Li6PS5Cl, which is a sulfide solid electrolyte) 130 is disposed only on the surface of the carbon material (activated carbon) 110. In contrast, in the cathode material 100 according to one embodiment of the present invention shown in FIG. 3B, the solid electrolyte (for example, Li6PS5Cl, which is a sulfide solid electrolyte) 130 is disposed not only on the surface of the carbon material (porous carbon) 110 but also on the inner surface of the pores of the carbon material (porous carbon) 110. More specifically, a continuous phase made of the cathode active material (sulfur) 120 is filled inside the pores 110a, and the solid electrolyte 130 is disposed as a dispersed phase in the continuous phase. As a result, at least a part of the solid electrolyte disposed on the inner surface of the pores and at least a part of the cathode active material (sulfur) similarly disposed inside the pores are in contact with each other. In addition, the percentage of the pore volume of the pores having a pore diameter in the range of 1 to 4 nm to the pore volume of the pores having a pore diameter in the range of 1 to 100 nm among the pores of the conductive material is controlled to 20% or less. Here, whether or not the cathode active material or the solid electrolyte is disposed inside the pores of the conductive material can be confirmed using various conventionally known methods. For example, it is possible to perform elemental mapping of each material using energy dispersive X-ray spectroscopy (EDX) on an image of the cross section of a conductive material observed with a transmission electron microscope (TEM), and to confirm the arrangement of each material using the obtained elemental map and the count number of elements from each material relative to the count number of all elements as indicators.For example, in the case where the solid electrolyte contains phosphorus atoms and / or boron atoms, if there is no possibility that the phosphorus atoms and / or boron atoms are derived from other materials, it is possible to obtain the above element map for phosphorus and / or boron and confirm the arrangement of the solid electrolyte from its distribution. It is also possible to confirm the arrangement of the solid electrolyte from the ratio of the count number of phosphorus and / or boron to the count number of all elements in EDX. When the arrangement of the solid electrolyte is confirmed using the count number of elements derived only from the solid electrolyte as an index in EDX, if the ratio of the count number of elements derived only from the solid electrolyte to the count number of all elements in EDX is 0.10 or more, it can be determined that the solid electrolyte is arranged inside the pores of the conductive material. In addition, the value of the ratio is preferably 0.15 or more, more preferably 0.20 or more, even more preferably 0.26 or more, and particularly preferably 0.35 or more. The larger this value is, the more the solid electrolyte is arranged on the inner surface of the pores of the conductive material. Therefore, when the value of the ratio is within these ranges, the effect of the present invention can be more significantly exhibited. There is no particular restriction on the preferred upper limit of the ratio, but a preferred upper limit is, for example, 0.50 or less, and more preferably 0.45 or less.

[0070] According to the cathode material of the present embodiment having the above-mentioned configuration, in an electric device such as an all-solid-state lithium secondary battery using a cathode active material containing sulfur, it is possible to further reduce the internal resistance of the electric device. Although the mechanism by which such an excellent effect is achieved by adopting the configuration of the present embodiment is not completely clear, the following mechanism is presumed. That is, in order for a charge / discharge reaction to proceed in a cathode active material containing sulfur, it is necessary for charge carriers such as electrons and lithium ions to smoothly enter and exit the surface of the cathode active material. Here, when a cathode active material (sulfur) 120 is held inside a pore 110a of a conductive material such as a carbon material 110 as in the cathode material 100' shown in FIG. 3A, on the surface of the cathode active material (sulfur) 120 located deep inside the pore 110a, the entry and exit of electrons can proceed smoothly to some extent via the conductive material. However, since the solid electrolyte 130 is not arranged inside the pore 110a, the entry and exit of charge carriers such as lithium ions does not proceed smoothly on the surface of the cathode active material (sulfur) 120 located deep inside the pore 110a. As a result, the charge / discharge reaction does not proceed sufficiently in the positive electrode active material (sulfur) 120 located deep inside the pores 110a, causing problems such as an increase in internal resistance and a decrease in charge / discharge rate characteristics.

[0071] In addition, when the percentage of the pore volume of the pores having a pore diameter in the range of 1 to 4 nm to the pore volume of the pores having a pore diameter in the range of 1 to 100 nm among the pores of the conductive material constituting the positive electrode material exceeds 20%, the ratio of the pores having a relatively small pore diameter increases. Here, the positive electrode active material containing sulfur has a molecular size of less than about 1 nm, so it can penetrate into the inside of the pores of the conductive material (carbon material) and be supported. In contrast, the size of a single molecule of the solid electrolyte is large at about 2 nm, and it is also considered that the size is further increased by solvation depending on the manufacturing method. In that case, the solid electrolyte cannot penetrate into the inside of the pores having a pore diameter of about several nm. As a result, it is considered that the charge / discharge reaction does not proceed sufficiently, and problems such as an increase in internal resistance and a decrease in charge / discharge rate characteristics occur.

[0072] In contrast, as in the positive electrode material 100 shown in FIG. 3B, when the percentage of the pore volume of the pores having a pore diameter in the range of 1 to 4 nm to the pore volume of the pores having a pore diameter in the range of 1 to 100 nm among the pores of the conductive material is controlled to 20% or less, and the solid electrolyte 130 is held together with the positive electrode active material (sulfur) 120 on the inner surface of the pores 110a of the conductive material such as the carbon material 110, not only the inflow and outflow of electrons via the conductive material but also the inflow and outflow of charge carriers via the solid electrolyte 130 can proceed smoothly on the surface of the positive electrode active material (sulfur) 120 located deep inside the pores 110a. As a result, even around the positive electrode active material (sulfur) 120 located deep inside the pores 110a, a three-phase interface where the positive electrode active material, the conductive material, and the solid electrolyte coexist can be sufficiently formed, and the charge and discharge reaction can proceed sufficiently. As a result, it is considered that the internal resistance of the battery is sufficiently reduced, and the charge and discharge rate characteristics are significantly improved.

[0073] Although there is no particular limitation on the manufacturing method of the positive electrode material according to the present embodiment having the above-mentioned configuration, an example of the manufacturing method will be briefly described. As described in the Examples section below, first, a conductive material satisfying the pore volume profile specified in the present application is prepared using a conventionally known method. Here, the method of obtaining such a conductive material will be described by taking the case where the conductive material is a carbon material as an example. First, a mold such as ceramics and a carbon raw material such as resin are mixed and fired under an inert atmosphere. Then, the mold is dissolved with an acid to obtain a carbon material (conductive material) having a porous structure to which the shape of the mold is transferred. At this time, the pore size and pore volume of the obtained carbon material can be changed by appropriately adjusting the particle size of the mold and the compounding ratio of the carbon raw material.

[0074] Next, a solution is prepared by dissolving the solid electrolyte in an organic solvent, and the conductive material is dispersed therein to obtain a dispersion. After that, the solvent is removed, and then heat treatment is performed at a temperature of about 150 to 250 ° C. for about 1 to 5 hours. As a result, a conductive material in which the solid electrolyte is impregnated inside the pores of the conductive material is obtained. Next, the obtained conductive material is mixed with a positive electrode active material in a dry state, and further heat treatment is performed under the same conditions as above. As a result, the positive electrode active material melts and penetrates into the inside of the pores of the conductive material, and a composite material in which the positive electrode active material is arranged (filled) together with the solid electrolyte inside the pores of the conductive material is obtained. The composite material obtained in this way may be used as a positive electrode material as it is, but it is preferable to further add a solid electrolyte to the composite material, mix it, and process it with an apparatus such as a ball mill as necessary to obtain a positive electrode material.

[0075] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably within the range of 35 to 99 mass %, and more preferably within the range of 40 to 90 mass %. Note that this content value is calculated based on the mass of only the positive electrode active material excluding the conductive material and the solid electrolyte.

[0076] The positive electrode active material layer may further include a conductive assistant (one that does not hold a positive electrode active material or a solid electrolyte inside the pores) and / or a binder, and the specific form and preferred form thereof may be similarly adopted as those described in the section on the negative electrode active material layer above. Similarly, the positive electrode active material layer preferably further includes a solid electrolyte, and particularly preferably further includes a sulfide solid electrolyte. The specific form and preferred form of the solid electrolyte, such as the sulfide solid electrolyte, may be similarly adopted as those described in the section on the negative electrode active material layer above.

[0077] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 27 and the negative electrode current collector plate 25 may be made of the same material or different materials.

[0078] [Positive and negative leads] Although not shown in the figure, the current collector and the current collector plate may be electrically connected via a positive electrode lead and a negative electrode lead. As the constituent materials of the positive electrode and the negative electrode lead, materials used in known lithium secondary batteries may be similarly adopted. Note that the part taken out from the exterior is preferably covered with a heat-resistant insulating heat shrink tube or the like so as not to come into contact with peripheral devices or wiring, causing leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).

[0079] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in Figs. 1 and 2, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, a laminate film containing aluminum is more preferable as the exterior body because it can easily adjust the group pressure applied to the power generating element from the outside.

[0080] The stacked battery according to the present embodiment has a configuration in which a plurality of unit cell layers are connected in parallel, and thus has high capacity and excellent cycle durability, and is therefore suitable for use as a driving power source for EVs and HEVs.

[0081] While one embodiment of the lithium secondary battery has been described above, the present invention is not limited to the configuration described in the above embodiment, and may be modified as appropriate based on the claims.

[0082] For example, the type of battery to which the lithium secondary battery according to the present embodiment can be applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.

[0083] In addition, the secondary battery according to the present embodiment does not have to be an all-solid-state type. That is, the solid electrolyte layer may further contain a conventionally known liquid electrolyte (electrolytic solution). There is no particular limit to the amount of liquid electrolyte (electrolytic solution) that can be contained in the solid electrolyte layer, but it is preferable that the amount is such that the shape of the solid electrolyte layer formed by the solid electrolyte is maintained and leakage of the liquid electrolyte (electrolytic solution) does not occur.

[0084] The liquid electrolyte (electrolytic solution) that can be used has a form in which a lithium salt is dissolved in an organic solvent. Examples of the organic solvent that can be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), propylene carbonate (PC), butylene carbonate (BC), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL). Among these, from the viewpoint of further improving the rapid charging characteristics and output characteristics, the organic solvent is preferably a chain carbonate, more preferably at least one selected from the group consisting of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and more preferably selected from ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).

[0085] Examples of the lithium salt include Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3. Among these, the lithium salt is preferably Li(FSO2)2N (LiFSI) from the viewpoints of battery output and charge / discharge cycle characteristics.

[0086] The liquid electrolyte (electrolytic solution) may further contain additives other than the above-mentioned components. Specific examples of such compounds include ethylene carbonate, vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and 1-ethyl-2-vinylethylene carbonate. Examples of the additives include ethylene carbonate, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyl oxyethylene carbonate, methylene ethylene carbonate, and 1,1-dimethyl-2-methylene ethylene carbonate. These additives may be used alone or in combination of two or more. The amount of additive used in the electrolyte solution may be appropriately adjusted.

[0087] [Battery pack] A battery pack is a device that consists of multiple batteries connected together. More specifically, it is a device that uses at least two batteries and is configured in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.

[0088] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. Then, a large capacity, high output assembled battery (battery module, battery pack, etc.) suitable for a vehicle driving power source or an auxiliary power source that requires a high volumetric energy density and a high volumetric output density can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large capacity assembled battery can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.

[0089] [vehicle] The battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a battery with excellent long-term reliability and long life can be configured, and thus, by mounting such a battery, a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge can be configured. For example, if the battery or a battery pack formed by combining a plurality of batteries is used in a hybrid vehicle, a fuel cell vehicle, or an electric vehicle (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light vehicles, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles), the vehicle will have a long life and high reliability. However, the application is not limited to automobiles, and the battery pack can be applied to, for example, various power sources for other vehicles, such as moving bodies such as trains, and can also be used as a mounted power source for an uninterruptible power supply device or the like. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.

[0091] Example of test cell preparation [Comparative Example 1] (Preparation of solid electrolyte-impregnated carbon) In a glove box with an argon atmosphere with a dew point of -68°C or less, 0.500g of sulfide solid electrolyte (Ampcera, Li6PS5Cl) was added to 100mL of ultra-dehydrated ethanol (Fujifilm Wako Pure Chemical Industries, Ltd.), and the solution was stirred until it became transparent to dissolve the solid electrolyte in ethanol. 1.00g of carbon (Kansai Thermochemical Industries, Ltd., activated carbon, MSC-30) was added to the obtained solid electrolyte ethanol solution, and the carbon was thoroughly dispersed in the solution by stirring. The container containing this carbon dispersion was connected to a vacuum device, and the container was reduced in pressure to 1 Pa or less using an oil rotary pump while stirring the carbon dispersion in the container with a magnetic stirrer. Since ethanol, which is a solvent, volatilizes under reduced pressure, the ethanol was removed over time, and the carbon impregnated with the solid electrolyte remained in the container. After the ethanol was removed under reduced pressure in this way, the solid electrolyte-impregnated carbon was prepared by heating to 180°C under reduced pressure and performing heat treatment for 3 hours. The carbon used in this comparative example was measured according to the BJH method described in EP Barrett, LG Joyner and PP Palenda, J. Am. Chem. Soc., 73, 373 (1951), and the pore size distribution in the range of 1 to 100 nm is shown in Figure 4. The horizontal axis of Figure 4 is the pore size Dp [nm] of the carbon, and the vertical axis is the pore volume Vp [cm 3 / g]. Furthermore, the percentage of the pore volume of pores having a pore diameter in the range of 1 to 4 nm to the pore volume of pores having a pore diameter in the range of 1 to 100 nm was calculated to be 79%.

[0092] (Preparation of sulfur / solid electrolyte / carbon composites by hot impregnation of sulfur) In a glove box with an argon atmosphere at a dew point of -68°C or less, 2.50g of sulfur (manufactured by Aldrich) was added to 0.750g of the solid electrolyte-impregnated carbon prepared above and mixed thoroughly in an agate mortar, and the mixed powder was then placed in a sealed pressure-resistant autoclave and heated at 170°C for 3 hours to melt the sulfur and impregnate the solid electrolyte-impregnated carbon with the sulfur. This produced a sulfur / solid electrolyte / carbon composite material.

[0093] (Preparation of sulfur-containing positive electrode material) In a glove box with an argon atmosphere at a dew point of -68°C or less, 40 g of 5 mm diameter zirconia balls, 0.130 g of the sulfur / solid electrolyte-impregnated carbon prepared above, and 0.070 g of solid electrolyte (Li6PS5Cl, manufactured by Ampcera) were placed in a 45 mL capacity zirconia container, and processed at 370 rpm for 6 hours using a planetary ball mill (Premium line P-7, manufactured by Fritsch) to obtain a powder of sulfur-containing positive electrode material. The composition of the sulfur-containing positive electrode material was sulfur:solid electrolyte:carbon = 50:40:10.

[0094] In addition, by quantifying the content of the solid electrolyte contained inside the pores of the conductive material (carbon) constituting the powder of the sulfur-containing positive electrode material obtained above by EDX mapping, it was confirmed that the solid electrolyte was disposed inside the pores of the conductive material (carbon) together with the sulfur, which is the positive electrode active material.

[0095] (Preparation of test cells (all-solid-state lithium secondary batteries)) The battery was fabricated in a glove box with an argon atmosphere at a dew point of −68° C. or lower.

[0096] A cylindrical convex punch (10 mm diameter) made of SUS was inserted into one side of a cylindrical tube jig made by Macor (tube inner diameter 10 mm, outer diameter 23 mm, height 20 mm), and 80 mg of sulfide solid electrolyte (Li6PS5Cl, made by Ampcera) was inserted from the upper side of the cylindrical tube jig. Then, another cylindrical convex punch made of SUS was inserted to sandwich the solid electrolyte, and a solid electrolyte layer with a diameter of 10 mm and a thickness of about 0.6 mm was formed in the cylindrical tube jig by pressing it for 3 minutes at a pressure of 75 MPa using a hydraulic press. Next, the cylindrical convex punch inserted from the upper side was once removed, and 7.5 mg of the sulfur-containing positive electrode mixture prepared above was placed on one side of the solid electrolyte layer in the cylindrical tube, and a cylindrical convex punch (which also serves as a positive electrode current collector) was inserted from the upper side again and pressed for 3 minutes at a pressure of 300 MPa to form a positive electrode active material layer with a diameter of 10 mm and a thickness of about 0.06 mm on one side of the solid electrolyte layer. Next, the lower cylindrical convex punch (which also served as the negative electrode current collector) was removed, and a lithium foil (manufactured by Nilaco Corporation, thickness 0.20 mm) punched to a diameter of 8 mm and an indium foil (manufactured by Nilaco Corporation, thickness 0.30 mm) punched to a diameter of 9 mm were stacked as the negative electrode. The cylindrical tube jig was inserted from the bottom so that the indium foil was positioned on the solid electrolyte layer side, and the cylindrical convex punch was inserted again and pressed at a pressure of 75 MPa for 3 minutes to form a lithium-indium negative electrode.

[0097] In this manner, a test cell (all-solid-state lithium secondary battery) was produced in which a negative electrode current collector (punch), a lithium-indium negative electrode, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector (punch) were stacked in this order.

[0098] [Example 1] An all-solid-state lithium secondary battery was produced in the same manner as in Comparative Example 1, except that in the preparation of the solid electrolyte-impregnated carbon, porous carbon powder (Knobel (registered trademark) P(3)010, manufactured by Toyo Tanso Co., Ltd.) was used as the carbon instead of MSC-30. Note that, in this example as well, it was confirmed that the solid electrolyte was disposed inside the pores of the conductive material (carbon) together with sulfur, which was the positive electrode active material.

[0099] Here, for the carbon used in this example, a graph of the pore size distribution in the range of 1 to 100 nm measured according to the BJH method described in EP Barrett, LG Joyner and PP Palenda, J. Am. Chem. Soc., 73, 373 (1951) is shown in Fig. 4. In addition, the percentage of the pore volume of pores in the range of 1 to 4 nm to the pore volume of pores in the range of 1 to 100 nm was calculated to be 9%.

[0100] [Example 2] In preparing the solid electrolyte-impregnated carbon, carbon black (Ketjenblack (registered trademark) EC600JD, manufactured by Lion Specialty Chemicals Co., Ltd.) was used instead of MSC-30 as carbon, and an all-solid-state lithium secondary battery was produced in the same manner as in Comparative Example 1. Note that, in this example as well, it was confirmed that the solid electrolyte was disposed inside the pores of the conductive material (carbon) together with sulfur, which was the positive electrode active material.

[0101] Here, for the carbon used in this example, a graph of the pore size distribution in the range of 1 to 100 nm measured according to the BJH method described in EP Barrett, LG Joyner and PP Palenda, J. Am. Chem. Soc., 73, 373 (1951) is shown in Figure 4. In addition, the percentage of the pore volume of pores in the range of 1 to 4 nm to the pore volume of pores in the range of 1 to 100 nm was calculated to be 20%.

[0102] <Test cell evaluation example> The internal resistance of the test cells prepared in each of the comparative examples and examples was measured by the following method. All of the following measurements were performed using a charge / discharge tester (HJ-SD8, manufactured by Hokuto Denko Corporation) in a constant temperature bath set at 25°C.

[0103] (Internal resistance measurement) The test cell was placed in the thermostatic chamber, and after the cell temperature had stabilized, a current of 0.2 mA / cm was applied for cell conditioning. 2 The cell was discharged at a constant current density of 0.5 V to a cell voltage of 0.5 V, followed by a constant current / constant voltage charge to 2.5 V at the same current density with a cut-off current of 0.01 mA / cm 2 The charging and discharging capacity was calculated from the charge and discharge capacity obtained after repeating this conditioning charge and discharge cycle 10 times and the mass of the positive electrode active material contained in the positive electrode. The capacity per mass of the positive electrode active material (mAh / g) was then calculated from the capacity calculated in this manner (SOC50%) to 50% (SOC50%) with a discharge current of 0.2 mA / cm. 2 A constant current discharge was performed at a current density of 1 C. After a 30-minute pause, a discharge was performed for 10 seconds at a discharge rate of 1 C. From the voltage drop and current value at that time, the direct current resistance (DCR) was calculated according to Ohm's law and used as the internal resistance value of the test cell. The results are shown in Table 1 below. The internal resistance values ​​(DCR) shown in Table 1 are relative values ​​when the value in Comparative Example 1 is set to 1.

[0104] [Table 1]

[0105] From the results shown in Table 1, it can be seen that, according to the present invention, the internal resistance can be further reduced in an all-solid-state lithium secondary battery using a cathode active material containing sulfur. In addition, when the internal resistance values ​​of the cathodes of Example 1 and Example 2 were compared, the internal resistance value of Example 1, which has a smaller value of the percentage (Vp1-4nm / Vp@1-100nm), was reduced to about 80% of that of Example 2. From this, it is considered that in the present invention, the smaller the value of the percentage (Vp1-4nm / Vp@1-100nm) is, the more preferable it is from the viewpoint of reducing the internal resistance. [Explanation of symbols]

[0106] 10a Stacked battery, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film, 100,100' Positive electrode material, 110 Carbon materials (activated carbon, porous carbon), 110a pores, 120 Cathode active material (sulfur), 130 Solid electrolyte.

Claims

1. The positive electrode active material includes a conductive material having fine pores, a solid electrolyte, and a positive electrode active material including sulfur, at least a portion of the solid electrolyte and at least a portion of the positive electrode active material are disposed on inner surfaces of the pores so as to be in contact with each other; a continuous phase made of the positive electrode active material is filled inside the pores, and the solid electrolyte is disposed as a dispersed phase in the continuous phase; and A positive electrode material for an electric device, wherein, among the pores, a pore volume of pores having a pore diameter in the range of 1 to 4 nm accounts for 20% or less of a pore volume of pores having a pore diameter in the range of 1 to 100 nm.

2. 2. The positive electrode material for an electrical device according to claim 1, wherein said percentage is 9% or less.

3. 3. The positive electrode material for an electric device according to claim 1, wherein in an observation image of a cross section of the conductive material by TEM-EDX, a ratio of the count number of elements derived only from the solid electrolyte to the count number of all elements is 0.10 or more.

4. The positive electrode material for an electric device according to any one of claims 1 to 3, wherein the conductive material is a carbon material.

5. The positive electrode material for an electric device according to any one of claims 1 to 4, wherein the conductive material has a total pore volume of 1.0 mL / g or more.

6. The positive electrode material for an electric device according to any one of claims 1 to 5, wherein the conductive material has an average pore size of 50 nm or less.

7. The positive electrode material for an electric device according to any one of claims 1 to 6, wherein the solid electrolyte is a sulfide solid electrolyte.

8. 8. The positive electrode material for an electric device according to claim 1, wherein the solid electrolyte contains an alkali metal atom, and a phosphorus atom and / or a boron atom.

9. 9. The positive electrode material for an electrical device according to claim 8, wherein the alkali metal atom is a lithium atom.

10. A positive electrode for an electric device comprising the positive electrode material for an electric device according to any one of claims 1 to 9.

11. An electric device comprising the positive electrode for an electric device according to claim 10.

12. The electrical device of claim 11 , which is an all-solid-state lithium secondary battery.

Citation Information

Patent Citations

  • Sulfur positive electrode mixture and manufacturing method thereof, sulfur positive electrode, and lithium-sulfur solid-state battery

    JP2020161288A

  • Composite material of alkali metal sulfide and conducting agent

    WO2012102037A1